2019
DOI: 10.1371/journal.pone.0223809
|View full text |Cite
|
Sign up to set email alerts
|

Direct transport vs secondary transfer to level I trauma centers in a French exclusive trauma system: Impact on mortality and determinants of triage on road-traffic victims

Abstract: BackgroundTransporting a severely injured patient directly to a trauma center (TC) is consensually considered optimal. Nevertheless, disagreement persists regarding the association between secondary transfer status and outcome. The aim of the study was to compare adjusted mortality between road traffic trauma patients directly or secondarily transported to a level 1 trauma center (TC) in an exclusive French trauma system with a physician staffed prehospital emergency medical system (EMS).MethodsA retrospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 49 publications
(53 reference statements)
2
14
0
2
Order By: Relevance
“…This may, in part, explain why an association between secondary transfer and increased mortality has not been reported uniformly. A recent analysis 29 of a French regional trauma system found no increased mortality associated with secondary transfer . This might be expected to be comparable to the UK system, but the authors suggested that results may reflect the very specific system of physician‐led prehospital care within their trauma system.…”
Section: Discussionmentioning
confidence: 95%
“…This may, in part, explain why an association between secondary transfer and increased mortality has not been reported uniformly. A recent analysis 29 of a French regional trauma system found no increased mortality associated with secondary transfer . This might be expected to be comparable to the UK system, but the authors suggested that results may reflect the very specific system of physician‐led prehospital care within their trauma system.…”
Section: Discussionmentioning
confidence: 95%
“…Domain invariance was assessed through uniform and non-uniform differential item functioning (DIF) for age (6 categories), gender, and education level (3 categories); differences of ≥ 0.5 logits in item difficulties were considered meaningful [ 33 , 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, this study only considers patients who were admitted alive at the hospital. It is impossible to assess whether the number of severely traumatized patients who died in the pre-hospital setting has not increased [18].…”
Section: Limitationsmentioning
confidence: 99%